Effect of Different Treatments on Seed Germination and Seedling Growth of Burmese Grape (Baccaurea sapida Muell. Arg.) - Sherpa, N. T.; Chakraborty, A.; Bhowmick, N.; Devi, M. P.; Sahana, N.; Subba, S. (International Journal of Economic Plants, 2025)
The experiment was carried out during the months of July, 2017 to September, 2019 at instructional farm of Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal to evaluate the role of different chemicals on seed germination and seedling growth behaviour. Among the minor fruit crops, Burmese grape (Baccaurea sapida Muell. Arg.) was one of the most popular and potential minor fruit. The plants were propagated through seeds and seeds were recalcitrant in nature. The maximum germination percentage (%), germination value and mean germination time (days) were recorded. The data recorded from the experiment revealed that the seeds treated with thiourea 100 ppm for 12 hrs (T8) showed highest germination percentage(68.17%) followed by T4 (63.94%). The germination value was recorded highest in T8 (6.49) followed by T9 (5.44) and mean germination time (26.99 days) respectively. Seed treated with KNO3 at 100 ppm for 12 hrs also thrived good result on seed germination and germination value. The highest root length (9.94) was obtained from T9 followed by T4 (9.62) whereas highest shoot length (7.80) was recorded in T7 followed by both T8 and T5 (7.58). Highest total seedling length was obtained from T4 (16.96) followed by T9 (16.86). Seedling vigour index was found highest in (T8) treatment (1396.24) followed by T9 (1363.03). Total fresh weight was obtained from T9 (1.42) followed by T8 (1.34) whereas total biomass was obtained from whereas hot water treatment was recorded minimum results for all the characters over control.